Games as a motivational strategy to enhance english vocabulary among students of ninth grade “b” of basic education, afternoon session at unidad educativa Manuel Agustin Cabrera Lozano in the city of Loja during the 2018-2019 school year - Quezada Gualán, Kerly María (2019)
The general objective of this research work was to enhance English vocabulary through the application of games as a motivational strategy among students of ninth grade “B”. The methods applied for obtaining, analyzing and processing the data were the scientific, the descriptive, the analytic-synthetic and the statistical. Tests and questionnaires were applied at the beginning and at the end of the intervention plan in order to collect information about the knowledge and attitude of fourteen students at Unidad Educativa Manuel Cabrera Lozano. The results showed that students enhanced significantly their vocabulary knowledge through games, Consequently, games are activities where students feel confidence to express ideas and opinions in class, to participate actively in the different activities and learn the language in a fun way.